Utilização de um sensor eletroquímico descartável para o diagnóstico rápido da COVID-19 por meio da detecção da proteína Spike do vírus SARS-CoV-2 - Nascimento, Evair Dias (2024)
The outbreak of the COVID-19 pandemic, caused by severe acute respiratory syndrome of Coronavirus 2 (SARS-CoV-2), has fueled the search for diagnostic tests aimed at controlling and reducing viral transmission. The reverse transcription polymerase chain reaction (RT-PCR) technique is the main technique used for diagnosis. However, due to accessibility and cost limitations, it is necessary to develop new tests that are more accessible and can help in the early diagnosis of the disease. With this in mind, we developed an ultrasensitive magnetic assay using magnetic beads and gold nanoparticles conjugated with the human angiotensin-converting enzyme 2 (ACE2) peptide (Gln24-Gln42) for the capture and detection of the SARS-CoV-2 Spike protein in samples of human saliva and urine. The technique applied involved the use of a disposable electrochemical device containing eight independent screen-printed carbon electrodes (SPCE) that allow the simultaneous analysis of eight samples. The magnetic assay exhibited ultra-low detection limits for SARS-CoV-2 Spike protein, 0.35 ag mL−1 in saliva samples and 0.13 ag mL−1 in urine samples. In terms of efficiency, the magnetic assay proposed for saliva samples, considering saliva samples from healthy individuals and those infected by SARS-CoV-2, presented an area under the curve (AUC) of 99.6%, sensitivity of 100.0% and specificity of 93.7% for the SARS-CoV-2 Spike protein and great similarity with the RT-PCR technique. The proposed approach for urine samples, considering urine samples from non-hospitalized negative individuals (Neg-NH), hospitalized negative individuals (Neg-H) and hospitalized positive individuals (Pos-H), showed significant similarity with the RT- technique. PCR, with area under the curve (AUC) of 87.0%, area under the precision curve (AUC-PR) of 73%, Sensitivity of 95.8% and Specificity 73.1%, for the Spike protein SARS-CoV-2. The results obtained point to the potential application of this magnetic assay as a simple and low-cost solution for point-of-care diagnosis of COVID-19 based on saliva or urine.